AN ENCRYPTION ALGORITHM EMPLOYING GRAPHS - Bipanchy Buzarbarua; Parismita Phukan; Mridusmita Das; Bikash Barman (Journal of Mechanics of Continua and Mathematical Sciences)
With the advancement of technology, maintaining secrecy is a crucial concern that requires a variety of skills. A scientific method for protecting communication against unauthenticated access is cryptography. In cryptography, there are several encryption techniques for data security. It has been suggested that new nonstandard encryption techniques are needed to shield communication from conventional threats. This work presents a method that uses graphs together with some algebraic features to provide some new encryption techniques for safe message transfer. The transmission of secret communications will be safer because of the suggested encryption techniques.